The Correlation between Gross Motor Function Classification System and Spasticity in Children with Cerebral Palsy - Ika Rosdiana; Ariestiani Ariestiani (Universitas Islam Sultan Agung, 2021)
Gross Motor Function Classification System (GMFCS) was used as a criterion to classify motor function in children with cerebral palsy. Spasticity is an increase in muscle resistance to passive stretching, which is an involuntary muscle activity associated with upper motor neuron paralysis that occurs in CP children so that it interferes with their activities. The purpose of this study was to determine the relationship between GMFCS and the level of spasticity assessed by the Ashworth scale in children with cerebral palsy. The analytical research method was observational with a cross sectional approach, the independent variable was assessed on the functional scale using the GMFCS and the dependent variable was assessed for spasticity using the Ashworth scale. The research sample was CP children at YPAC Semarang city. The results of this study are that the highest GMFCS level in children with cerebral palsy at SLB YPAC Semarang City is level III and IV as much as 25.0% while the assessment of spasticity using the ashworth scale obtained ashworth level 3 as much as 58.3% while the results of the calculation of the non-parametric Spearman correlation test were obtained. p value = 0.000 (p < 0.05) with a value of r = 0.837. Therefore, it can be concluded that there is a positive correlation between GMFCS and the level of spasticity assessed using the Ashworth scale in children with cerebral palsy.